Validation of proposed criteria for progressive pulmonary fibrosis. - Pugashetti,JV; Adegunsoye,A; Wu,Z; Lee,CT; Srikrishnan,A; Ghodrati,S; Vo,V; Renzoni,EA; Wells,AU; Garcia,CK; Chua,F; Newton,CA; et al. (American Journal of Respiratory and Critical Care Medicine, 2022)
RATIONALE: Criteria for progressive pulmonary fibrosis (PPF) have been proposed, but their prognostic value beyond categorical decline in forced vital capacity (FVC) remains unclear. OBJECTIVE: To determine whether proposed PPF criteria predict transplant-free survival (TFS) in patients with non-idiopathic pulmonary fibrosis (IPF) forms of interstitial lung disease (ILD). METHODS: A retrospective, multi-center cohort analysis was performed. Patients diagnosed with fibrotic connective tissue disease associated ILD, fibrotic hypersensitivity pneumonitis and non-IPF idiopathic interstitial pneumonia from three US centers and one UK center comprised test and validation cohorts, respectively. Cox proportional hazards regression was used to test the association between five-year TFS and 10% FVC decline, followed by thirteen additional PPF criteria satisfied in the absence of >=10% FVC decline. MAIN RESULTS: One thousand three hundred forty-one patients met inclusion criteria. A >=10% relative FVC decline was the strongest predictor of reduced TFS and showed consistent TFS association across cohorts, ILD subtypes and treatment groups, resulting in a phenotype that closely resembled IPF. Ten additional PPF criteria satisfied in the absence of >=10% relative FVC decline were also associated with reduced TFS in the US test cohort, with six maintaining TFS association in the UK validation cohort. Validated PPF criteria requiring a combination of physiologic, radiologic, and symptomatic worsening performed similarly to their stand-alone components but captured a smaller number of patients. CONCLUSIONS: An FVC decline of >=10% and six additional PPF criteria satisfied in the absence of such decline identify non-IPF ILD patients at increased risk of death or lung transplant.